2019
DOI: 10.1177/1129729819826029
|View full text |Cite
|
Sign up to set email alerts
|

Arteriovenous fistula creation in a patient without a pulse: Vascular access in patients with left ventricular assist devices

Abstract: Left ventricular assist devices are used in heart failure patients as bridge to transplantation or increasingly as a destination therapy. These patients frequently have renal dysfunction and many reach end-stage renal failure. If haemodialysis is required, minimization of infection risk is essential. Arteriovenous grafts have been recommended for these patients due to hypothetical concerns regarding fistula maturation due to continuous flow. A case is described where a brachiocephalic arteriovenous fistula was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…The third one was free of any complications or further intervention. Khawaja et al described a successful case of brachial-cephalic AVF used for dialysis without further intervention [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The third one was free of any complications or further intervention. Khawaja et al described a successful case of brachial-cephalic AVF used for dialysis without further intervention [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…6 While the lack of pulsatility was theorized to lead to uncertainty of fistula maturation in the setting of continuous flow support, several authors have reported long-term success in this setting with excellent AVF maturation for use in dialysis. [8][9][10] Now, Hair and colleagues 7 also confirm that AVF can be successfully matured in a circulation supported by a TAH with mechanically induced pulsatile flow. It is, however, important to note that the shunt created by a mature AVF may reach 600 to 1200 mL/min, 4 and the risk of elevating pulmonary vascular resistance should be factored into the decision to pursue an AVF in a bridge-to-transplant candidate.…”
mentioning
confidence: 87%
“…83 Several cases of successful arteriovenous fistula placement, maturation, and use have been reported. 84,85 Concerns remain, however, about arteriovenous fistula maturation in the setting of low pulsatile blood flow, and others have advocated for arteriovenous grafts as the preferred access. 86 Peritoneal dialysis is an option as modern LVADs do not compromise the peritoneal space.…”
Section: Clinical Considerationsmentioning
confidence: 99%
“…Arteriovenous access placement, and avoidance of long-term tunneled catheter use, is desirable given the elevated risk of bloodstream infections with dialysis catheters (82). Several cases of successful arteriovenous fistula placement, maturation, and use have been reported (83,84). Concerns remain, however, about arteriovenous fistula maturation in the setting of low pulsatile blood flow, and others have advocated for arteriovenous grafts as the preferred access (85).…”
Section: Durable Mcsmentioning
confidence: 99%